Analysis Of Strategies For Increasing The Potential Of Digital-Based MSMEs Using A Triple Bottom Line Approach To Implement A Green Economy In Border Areas - Siokalang, Maria Angela; Dedy, Dedy; Atlantika, Yeremia Niaga; Efrata, Rediko (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study uses the Triple Bottom Line approach to analyze strategies for increasing the potential of digital-based MSMEs to implement a green economy in border areas. In the digital context, it is urgent to study this topic because MSMEs that cannot adapt to information technology risk being left behind. Therefore, it is important to identify strategies that can support the transformation and competitiveness of MSMEs in the market. Integrating the principles of the green economy and the Triple Bottom Line emphasizes balancing social, economic, and environmental dimensions while encouraging innovation and collaboration between the government, private sector, and community. This research was conducted using qualitative methods. Data sources were obtained through observation, a literature study, questionnaires, and in-depth interviews with respondents from four MSME clusters in border areas. MSME clusters were grouped into three categories: creative industries, services, and culinary. Data validation was carried out in the form of problem-based learning (PBL)-based focus group discussions (FGDs) with all informants. The results of this study describe strategies to improve MSME human resources, including building a digital education platform, training digital practitioners, strengthening infrastructure, branding, product differentiation, and designing a digital payment system.